True colors: Costumers`packaging choices depend on color of retail environment - Martinez, L. M.; Rando, B.; Agante, Luisa; Abreu, A. M. (Journal of Retailing and Consumer Services, 2021)
Color is one of the most elementary techniques used in marketing and produces behavioral effects reflecting purchase attitudes. However, packaging color has seldom been investigated in-context. Additionally, color research mainly focuses on individual colors, instead of color combinations. Here, we aim to study the putative effect that dominant retail environment colors might produce on attractiveness and product purchase intention, when products use similar store colors, and when products use complementary colors to those of the store. Moreover, we investigate if these choices are product dependent (e.g., do food and non-food products evoke the same packaging color choices in a given retail color context). A total of 653 participants were recruited to participate in two experimental studies disseminated through online platforms. Study 1 showed an interaction between store and product color significantly affecting both product attractiveness and purchase intention. Importantly, we found that the product category might modulate the complementary color-effect, in terms of attractiveness and purchase intention. Study 2 revealed that product-type subtends sensorial experience or semantic derivation mechanisms for preferred color choices. Together these studies unveil a complex relation between product type, context and color that possibly subtend different cognitive decision-making mechanisms. As such, colors cannot be considered as standalone variables in consumer decision making strategies. Here, we shed light into color perception and product strategy, thus helping marketers, retailers and designers to communicate more efficiently and to define a successful brand strategy.